The importance of pediatric dental intervention in promoting well-being in children who demonstrate non-nutritive sucking behaviors: A systematic review of the literature (Research, Society and Development, 2023)
The pediatric dentist's approach to managing the harmful behaviors of harmful non-nutritive sucking habits for the prevention and treatment of orofacial deformities is of fundamental importance in promoting children's orofacial health. The early identification of harmful habits through clinical and complementary examinations makes it possible to create an individualized treatment plan, considering the specific characteristics of each case. Appropriate intervention, based on scientific evidence, aims to interrupt the habit, correct orofacial changes and reestablish adequate orofacial development. In the meantime, the objective of this article was to carry out an analysis of the importance of pediatric dentistry intervention in promoting well-being in children who present non-nutritive sucking behaviors. This is a systematic literature review, developed through searches for publications obtained in the databases: PubMed, SciELO and Google Scholar. The descriptors sucking behavior, pediatric dentistry, stomatognathic system and oral health were used. In the end, we selected (29) publications to compose the study. Through the analysis of the articles, it was possible to demonstrate that through an interdisciplinary approach and a favorable prognosis, it is possible to achieve satisfactory results, improving well-being and preventing future complications in children affected by harmful non-nutritive sucking habits.